Investigating the Barriers of Using Blockchain Technology in Iran's Automobile Industry - Mohsen Zabihi Jamkhaneh; Mojtaba Farrokh; Hamed Hashemi Nezhad Mikal; Milad Sheikh Reza Zadeh Tehrani (International Journal of Web Research, 2022)
This study evaluated the obstacles and challenges of using blockchain technology in Iran's automotive industry. The statistical population of the present study is all specialists and experts who were familiar with blockchain technology. However, because of the impossibility of identifying and studying all the people in the society and the lack of access to all of them, sampling was done employing a purposeful judgment method. Accordingly, ten academic and industrial experts were selected as the expert. In this study, a document study was applied to study the theoretical backgrounds and the related literature. Thus, the latest materials and concepts related to the subject were reviewed by referring to scientific sources, including books, articles, and theses. A survey method was also used in evaluating obstacles and challenges. At this stage, a researcher-made questionnaire was employed to collect experts' views. The process of conducting this research is as follows: first, the theoretical backgrounds and the related literature were examined. Then the questionnaire of the study was designed, distributed among the experts, and collected. After that, the data was analyzed using the Fuzzy Dematel Technique. Based on the findings, among the seven factors of the leading technical and technological component, three sub-components, including the lack of necessary safety against cyber attacks, the storing information problem, and the lack of standardization in different blockchain systems were ranked first to third, respectively, which shows the significance of the technical and technological factors.